(untitled) (Indian Journal of Arid Horticulture, 2025)
Aonla (Emblica officinalis Gaertn.), also known as Indian gooseberry, is the emerging fruit crop with lot of scope for commercial cultivation with its wider adoptability across India. It comes up well in black saline soil, dry lands, with less pest incidence, prolonged storability, high medicinal value and thereby greater demand in pharmaceutical, cosmetic and food industry. Recently role of extension has been stretched beyond production and market information has been brought under its purview to facilitate the farmer in fetching good price for his produce. Marketing of aonla fruits has become important aspect in view of its greater demand from various sectors. Keeping this in view, a study was conducted to assess the method of marketing of aonla fruits by the farmers. The study was conducted in Panchmahals and Vadodara districts of Gujarat. The list of aonla farmers was prepared and thirty farmers were randomly selected. A structured interview schedule was prepared to assess the marketing of aonla fruits by the aonla farmers.